Derivation and validation of a clinical decision rule to risk‐stratify COVID‐19 patients discharged from the emergency department: The CCEDRRN COVID discharge score. Issue 6 (22nd December 2022) - Brooks, Steven C.; Rosychuk, Rhonda J.; Perry, Jeffrey J.; Morrison, Laurie J.; Wiemer, Hana; Fok, Patrick; Rowe, Brian H.; Daoust, Raoul; Vatanpour, Shabnam; Turner, Joel; Landes, Megan; Ohle, Robert; et al.
Abstract: Objective: To risk‐stratify COVID‐19 patients being considered for discharge from the emergency department (ED). Methods: We conducted an observational study to derive and validate a clinical decision rule to identify COVID‐19 patients at risk for hospital admission or death within 72 hours of ED discharge. We used data from 49 sites in the Canadian COVID‐19 Emergency Department Rapid Response Network (CCEDRRN) between March 1, 2020, and September 8, 2021. We randomly assigned hospitals to derivation or validation and prespecified clinical variables as candidate predictors. We used logistic regression to develop the score in a derivation cohort and examined its performance in predicting short‐term adverse outcomes in a validation cohort. Results: Of 15, 305 eligible patient visits, 535 (3.6%) experienced the outcome. The score included age, sex, pregnancy status, temperature, arrival mode, respiratory rate, and respiratory distress. The area under the curve was 0.70 (95% confidence interval [CI] 0.68–0.73) in derivation and 0.71 (95% CI 0.68–0.73) in combined derivation and validation cohorts. Among those with a score of 3 or less, the risk for the primary outcome was 1.9% or less, and the sensitivity of using 3 as a rule‐out score was 89.3% (95% CI 82.7–94.0). Among those with a score of ≥9, the risk for the primary outcome was as high as 12.2% and the specificity of using 9 as a rule‐in score was 95.6% (95% CI 94.9–96.2). Conclusion: The CCEDRRN COVID discharge score can identify patients at risk of short‐term adverse outcomes after ED discharge with variables that are readily available on patient arrival.